2021
DOI: 10.26714/jkmi.16.4.2021.240-245
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan antara Penggunaan Kontrasepsi Hormonal dengan Kejadian Hipertensi pada Wanita Usia Subur di Indonesia (Analisis Data Indonesian Family Life Survey 5)

Abstract: Background: The incidence of hypertension in women is 36.9%, allegedly related to hormonal changes triggered by the use of hormonal contraceptives. This study aims to analyze the relationship between the use of hormonal contraception on the incidence of hypertension in women of childbearing age. Methods: This cross-sectional study used IFLS 2014 data and involved 7,097 participants who were selected using multistage random sampling technique. The research variables included age, education, work status, physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
1
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
0
1
2
Order By: Relevance
“…The results of this study are not in line with Yuniarti and Rosyada (2021) who found in their research results that there is a relationship between age and the incidence of hypertension with a p-value of 0.000 and a PR value of 2.226 (95% CI: 2.065 -2.399), which means that people aged ≥ 35 years have 2.226 times the risk of developing hypertension compared to <35 years. This is also in line with research conducted by Kiber et al, (2019) which showed that increasing age had a 3.31 times greater likelihood of experiencing hypertension (AOR 3.31,CI 1.00,10.99).…”
Section: Agecontrasting
confidence: 99%
“…The results of this study are not in line with Yuniarti and Rosyada (2021) who found in their research results that there is a relationship between age and the incidence of hypertension with a p-value of 0.000 and a PR value of 2.226 (95% CI: 2.065 -2.399), which means that people aged ≥ 35 years have 2.226 times the risk of developing hypertension compared to <35 years. This is also in line with research conducted by Kiber et al, (2019) which showed that increasing age had a 3.31 times greater likelihood of experiencing hypertension (AOR 3.31,CI 1.00,10.99).…”
Section: Agecontrasting
confidence: 99%
“…Prevalensi hipertensi pada penduduk usia ≥ 18 tahun lebih banyak pada kelompok perempuan yaitu sebesar 36,9% dibandingkan laki-laki yaitu sebesar 31,34%. Di samping itu, pengontrolan hipertensi belum adekuat meskipun obat-obatan yang efektif banyak tersedia (Yuniarti, 2019).…”
Section: Endemis Journalunclassified
“…Sejalan juga dengan penelitian yang dilakukan oleh (Yuniarti, 2019) diperoleh hasil nilai secara signifikan yaitu 0,061 (>0,05) yang berarti tidak terdapat hubungan antara riwayat penggunaan KB dengan kejadian hipertensi pada wanita. Hal ini disebabkan para wanita lebih memilih menggunakan kondom atau kalender daripada harus menggunakan KB IUD.…”
Section: Metode Penelitianunclassified